HUBUNGAN PENGETAHUAN AKSEPTOR KB SUNTIK 3 BULAN (DMPA) DENGAN PERILAKU PENANGANAN EFEKSAMPING DI PUSKESMAS KLAKAH KECAMATAN KLAKAH LUMAJANG - Sari, Iin Nur Indah; Hikmawati, Nova; Wahyuningsih, Sri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The success indicator of the family planning program is determined by the quality of service, one of which is the provision of quality counseling to both old and new acceptors. If counseling that can give knowledge to dissenters is lacking, it can cause problems one of the following is bad manners to manage birth control side effects. A growing knowledge of side effects can promote a positive attitude in dealing with those side effects (Yuliari, 2019). This study aims to determine the correlation between knowledge of 3-month injection family planning acceptors and the behavior of handling side effects. The research used analytic correlation with a cross-sectional approach model. The population in this study was all 3-month injector birth control in Klakah health center of the Mei-Juni as many as 32 patients. The sample used as many as 32 responders. The sampling technique used is total Sampling. This research data collection USES a questionnaire. Data processing techniques use editing, coding, scoring, and tabulating. Data analysis uses the chi-square). The results of the research by testing the correlation with Chi-Square showed that at a significant level of 0.05, the correlation was obtained with a probability number of P-Value Chi-Square = 0.005. The significant value of the two variables is 0.005 < 0.05, which means that P-Value Chi-Square (Ho is rejected and Ha is accepted), so it can be concluded that there is a correlation between knowledge of 3 months injectable family planning acceptors and behavior in handling side effects in the Klakah health center.